The edge of place - Sullivan, Emily, author; Osborne, Erika, advisor; Badia, Lynn, committee member; Dineen, Mark, committee member; Moore, Emily, committee member (Colorado State University. Libraries, 2019)
My thesis work uses clouds as a metaphor to explore transition, change, and shifts. I track the origins of my interest in landscape painting by discussing nineteenth century Hudson River School painters — the first to celebrate the American landscape in a traditional oil painting method. Their practice of painting en plein air, in addition to their mobile studio practices as artist-adventurers, influences my paint language and approach. Frederic Church's painted cloud sketches are highlighted for his process, materials, and relationship to place. I argue that these paintings, both finished and unfinished, exist in a state of liminality. Next, I detail a search for the "local" in the presence of multicenteredness and movement, as outlined in Lucy Lippard's text, The Lure of the Local. In my series Holding Patterns, and my thesis work The Edge of Place, I question what it means to find a sense of place within shifting localities. I reference contemporary approaches to landscape and skyscape painting within the context of Lippard's discussion. The history of liminality is followed, using anthropologist Victor Turner's work as a launching point to discuss how liminal spaces are illustrated in my paintings. My work is also supported by Rebecca Solnit's text A Field Guide to Getting Lost to show how relationships in flux can be mirrored in the landscape. Finally, time as a marker of liminality is discussed within the context of my paintings.
Keywords: liminality; place; sky; painting; clouds; plein air